(3SLd JGQjN GdESJYeGQ aj GdLRGFQ (B/s - (3Sja GdESdGe, GdRHjQ s ((3GdLRGFQ (B:s (3GdeDSSI GdLRGFQjI ddWHGYI ,s, 1988)
(3YfOeG GJLgJ GdMedI GdYScQjI GdaQfSjI Gdi GdLRGFQ cGfJ aj XGgQgG CNP KCQ NQGaI GdeQhMI ef OGi GdLRGFQ h gj aj GdMbjbI cGfJ JMed fhGjG CNHK hCHYO ef Pdc GP de JeQ CjGe Hd SGYGJ eYOhOI (B, (3ef ONhd GdbhGJ GdaQfSjI Gdi GdeOjfI MJi HOCJ JJVM fhGjG GdMedI GdaQfSjI GdbQjHI efgG h GdHYjOI (B, (3TjFG aTjFG (B.(3h bHd gPG GdJGQjN cGfJ aQfSG GdGSJYeGQjI aj GdQHY GdGhd ef GdbQf GdJGSY YTQ JHMK Yf GdJhSY h GdNQhL ef GdbGQI GdGhQHjI h cGfJ JegO dgPG GdJhSY GdGSJYeGQj GdXGde GdNHjK h GdNQhL ef gPg GdbGQI GdJj HOCJ GdGMJcGQGJ GdQCSeGdjI JSYi Gdi GjLGO CShGb NGQLjI dJShjb efJhLGJgG (B.s
Keywords: (3GdLRGFQ s; (3JGQjN s; (3GdESJYeGQ s; (3SLds